Development of the ADILUHUNG PADUKA training module to enhance drivers’ technical skills, service ethics, and legal awareness at Universitas Negeri Yogyakarta - Karsono Wibowo; Siswantoyo Siswantoyo; Sefina Triastuti (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2025)
This study aims to develop the ADILUHUNG PADUKA training module to enhance the technical skills, service ethics, and legal awareness of official drivers at Universitas Negeri Yogyakarta (UNY). Drivers, as frontline representatives of the institution, play a strategic role in shaping the university’s public image and ensuring safe and efficient transportation services. Using a Research and Development (R&D) approach, this study employed a modified Borg and Gall model consisting of needs analysis, design, initial product development, expert validation, limited field testing, product revision, effectiveness evaluation, and dissemination. A total of 48 active drivers and one vehicle coordinator participated in the study. Data were gathered through surveys, interviews, observations, and expert and user validation instruments. Quantitative and qualitative analyses were conducted to evaluate module feasibility. The results demonstrate that the ADILUHUNG PADUKA module meets high standards of content validity, instructional design quality, and practical usability. Expert validation across sessions—driving safety, service ethics, and legal awareness—rated the module as “Very Effective,” while driver responses positioned all practicality indicators in the “Very Good” category. The module significantly improved drivers’ technical competence, professional behavior, and understanding of legal responsibilities. The findings indicate that the training module is feasible for institutional implementation and has the potential for adaptation by other higher education institutions seeking to standardize driver professionalism and strengthen transportation service quality.